2020
DOI: 10.1002/jeq2.20123
|View full text |Cite
|
Sign up to set email alerts
|

Surface soil liming reduces cadmium uptake in cacao seedlings but subsurface uptake is enhanced

Abstract: Cadmium concentrations in cacao (Theobroma cacao L.) beans from South America often exceed trade limits. Liming soil is advocated as a remediation option, but amendments cannot be incorporated into the entire root zone without harming the trees. An experiment was set up to identify how Cd uptake varies within the root zone when surface and subsurface soil layers are either limed or not. The experiment used 22-cm-height pots with top and bottom layers using surface and subsurface soil samples from a cacao field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 35 publications
0
20
0
1
Order By: Relevance
“…In 30 established plantations, lime incorporation to deeper soil horizons is not possible without damaging the root system, which may compromise the efficacy of the amendment. Indeed, Argüello et al (2020) showed in a pot experiment with cacao seedlings that partially liming the rooted soil (lime in top compartment only as would be the case in field liming), enhanced Cd uptake from the non-limed bottom compartment.…”
Section: Limementioning
confidence: 99%
See 1 more Smart Citation
“…In 30 established plantations, lime incorporation to deeper soil horizons is not possible without damaging the root system, which may compromise the efficacy of the amendment. Indeed, Argüello et al (2020) showed in a pot experiment with cacao seedlings that partially liming the rooted soil (lime in top compartment only as would be the case in field liming), enhanced Cd uptake from the non-limed bottom compartment.…”
Section: Limementioning
confidence: 99%
“…However, this effect was only found in soils spiked to Cd concentrations well above environmentally relevant soil Cd concentrations. Argüello et al (2020) found that Cd uptake in cacao from deeper soil layers was enhanced by surface liming and the authors related this to increased activity of deeper roots to cope with micronutrient deficiency in the topsoil (i.e. Zn) caused by surface liming.…”
Section: Bean Cadmium Concentrations and Their Relationship With Soil Properties: A Metaanalysismentioning
confidence: 99%
“…The application of lime and biochar to Cd contaminated soils have been shown to be effective in mitigating Cd uptake into the cacao tree and into the beans (Ramtahal et al 2018;. However, a number of studies have recommended that the method of application needs to be improved in order to improve the effectiveness of the soil ameliorants under eld conditions (Argüello et al 2020;Ramtahal et al 2018Ramtahal et al , 2019. The effectiveness of the various methods of application were explored in this study based on (a) the time taken for the amendment to take effect (b) the magnitude of reduction in leaf Cd and (c) the duration of effectiveness compared to the control.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a very recent paper (Liu et al 2021) shows the benefits of dolomite phosphate rock (DPR), humic acid-activated dolomite phosphate rock (ADPR) and biochar (BC) in immobilizing Cd in subtropical soils. However, regarding the application in cocoa crops during the past years, although the application of liming material such as dolomite it has been extensively studied as an option to stabilize Cd in the soil, neutralize acidic soil and enhance metal stabilization in soil by reducing the extractable Cd concentration (Hamid et al 2018;Ramtahal et al 2019;Argüello et al 2020), it has been shown that this technique needs to be reconsidered due to its efficiency in terms of time and cost for cacao in field. Furthermore, the chloride ions released from the application of KCl fertilizers, might form Cd-Cl soluble compounds, increasing Cd bioavailability (Nino-Savala 2019), which could be the case in farms A, B and D, where the application of KCl is regularly used.…”
Section: The Role Of Fertilizers and Amendments As CD Inputmentioning
confidence: 99%